SARS-CoV-2 IgG seropositivity after the severe Omicron wave of COVID-19 in Hong Kong. Issue 1 (31st December 2022) - Poon, Rosana Wing-Shan; Chan, Brian Pui-Chun; Chan, Wan-Mui; Fong, Carol Ho-Yan; Zhang, Xiaojuan; Lu, Lu; Chen, Lin-Lei; Lam, Joy-Yan; Cheng, Vincent Chi-Chung; Wong, Samson S. Y.; Kok, Kin-Hang; Yuen, Kwok-Yung; et al.
ABSTRACT: The SARS-CoV-2 Omicron variant has led to a major wave of COVID-19 in Hong Kong between January and May 2022. Here, we used seroprevalence to estimate the combined incidence of vaccination and SARS-CoV-2 infection, including subclinical infection which were not diagnosed at the acute stage. The overall seropositive rate of IgG against receptor binding domain (anti-RBD IgG) increased from 52.2% in December 2021 to 89.3% in May 2022. The level of anti-RBD IgG was lowest in the 0–9 and ≥80 year-old age groups in May 2022. The seropositive rate of antibody against ORF8, which reflects the rate of prior infection, was 23.4% in May 2022. Our data suggest that although most individuals were either vaccinated or infected after the fifth wave, children and older adults remain most vulnerable. Public health measures should target these age groups in order to ameliorate the healthcare consequences of upcoming waves.